INTRODUCTION TO INTERNATIONAL CRIMINAL LAW - Nobuo Hayashi (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2008)
In discourse of international criminal law, today, individual criminal responsibility is an important principle. This principle will be explained along with other aspects, such as "secondary rules' "actus reus' "mens rea" and c,lso some international crimes under international law, particularly genocide, crimes against humanity, and war crimes. While, the international legal mechanisms, such as ICC and ICTY are also presented in this paper in connection with the implementation of international criminal responsibility. Key words: individual criminal responsibility, criminal conduct, international criminal law.